THE EFFECT OF INCOME AND ELECTRONIC MONEY ON CONSUMPTION BEHAVIOR OF STUDENTS UNDERGRADUATE ECONOMIC FINANCE AND BANKING UNIVERSITAS BRAWIJAYA - Zanuadewi, Mellania Putri; Bintoro, Nugroho Suryo (Contemporary Studies in Economic, Finance and Banking, 2024)
This research was conducted to determine the effect of Income and Electronic Money (E-Money) on Consumption Behavior. This data specifically takes students of Economics, Finance and Banking, Universitas Brawijaya (Class of 2019 - 2021). This study uses a quantitative approach. The sampling method used in this research is purposive sampling. The method used in this study is the Partial Least Square (PLS) method with the SMARTPLS 3.0 tool. The sample of this study is 289 students who use E-money as a medium of exchange. And the results of the analysis show that the income variable has no significant effect on consumption behavior. Meanwhile, Electronic Money has a significant effect on Consumption Behavior of Students of S1 Economics, Finance and Banking, Universitas Brawijaya